Proporsi rumah berarsitektur Cina di tepian sungai Musi Palembang - Anjuma Perkasa Jaya (ARTEKS : Jurnal Teknik Arsitektur, 2019)
Since the era of Sriwijaya, Palembang had been accosted and livable by different ethnics from other nations, such as Chinese, Arabia, and Campa. Their presence has coloured the development of architecture in Palembang because of the architectural influences of the native country. The existence of the Chinese architecture houses in Musi river is one of the architectural heritages of the Chinese ethnic that still survive until today. Visually, the shape of the buildings provides equal image proportions indicating that there is a size comparison of the physical elements of the main building in building the houses. It is interesting to find out physical proportions (main frame) of those house buildings. The research used descriptive quantitative method and data were analysed stastistically. Results of the study showed that the proportion (ratio) of the physical elements (main frame) of this building was P: L: T = 9.2:3.4:2.3. The front roof of the building (segment A) has a high proportion but lower than the roofs on segment B and C. This indicates that the spaces on segments B and C have a higher space value as praying room and private activity spot for its residents. © 2019 Anjuma Perkasa Jaya